The secret garden - Burnett (Usborne Pub Ltd; UK, 2008)
Presents an abridged version of the story of ten-year-old Mary who, after the death of her parents, comes to live in a lonely house on the Yorkshire moors where she discovers an invalid cousin and the mysteries of a locked garden.